A new species of hintonelmis spangler (Coleoptera: Elmidae: Elminae) from Central Amazonia, Brazil - Fernandes, André Silva (Zootaxa, 2020)
Hintonelmis anamariae sp. nov. is described and illustrated based on adult specimens collected in Presidente Figueiredo Municipality, Amazonas State, Brazil. This species can be distinguished from all other known Hintonelmis species by its dorsal color pattern and the morphology of the male genitalia. Copyright © 2010 Magnolia Press.